High hydrophobic poly(lactic acid) foams impregnating one-step Si–F modified lignin nanoparticles for oil/organic solvents absorption. (June 2021) - Ding, Hui; Yang, Weijun; Yu, Wenhao; Liu, Tianxi; Wang, Haigang; Xu, Pengwu; Lin, Liangliang; Ma, Piming
Abstract: In this work, the hydrophobic lignin nanoparticles (LNP) were synthesized by a synchronous modification of silanization and fluorination process. Thermogravimetric analyser, fourier-transform-infrared-spectroscopy, X-ray photoelectron spectroscopy and transmission electron microscopy were used to confirm the surface modified LNP ( m -LNP). The maximum degradation temperature of m -LNP was 85 °C higher than that of origin LNP. Then the bio-based PLA foams were prepared via freezing-dry method by impregnating various amount of m -LNP. The results showed that a high hydrophobicity (141° of contact angle) and porosity structure (94% of porosity) were constructed when the m -LNP content increased to 6 wt% (PLA-6L). Afterwards, the absorption capacities of the PLA composite foams towards various oil/organic solvents are measured. The composite foams reached their saturated adsorption capacity in quite short time and exhibited good recyclability due to the two factors: high hydrophobicity and high porosity. Thus, the bio-based PLA/m-LNP composite foams could be used as the eco-benign and efficient absorbents for petroleum leakage, oil spills and toxic organic solvents in water contamination field. Highlights: Synchronous modification of LNP by silanization and fluorination was carried out through a wet chemical process. Bio-based hydrophobic PLA foams were prepared via freezing-dry method. A high hydrophobicity (141°) and porosity structure (94%) was constructed for PLA-6L sample. PLA composite foam showed good absorption capacity and absorption cycles.